2013
DOI: 10.1016/j.ijantimicag.2012.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Peptide nucleic acids inhibit growth of Brucella suis in pure culture and in infected murine macrophages

Abstract: Peptide nucleic acids (PNAs) are single-stranded, synthetic nucleic acid analogues containing a pseudopeptide backbone in place of the phosphodiester sugar–phosphate. When PNAs are covalently linked to cell-penetrating peptides (CPPs) they readily penetrate the bacterial cell envelope, inhibit expression of targeted genes and cause growth inhibition both of Gram-positive and Gram-negative bacteria. However, the effectiveness of PNAs against Brucella, a facultative intracellular bacterial pathogen, was unknown.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 22 publications
0
38
0
Order By: Relevance
“…Rajasekaran et al have studied the inhibition of Brucella suis growth using PNA linked covalently to cell-penetrating peptides (CPPs) [2]. After 24 hour of treatment, Brucella genes are involved in DNA, RNA, cell envelope, fatty acid and protein synthesis that are inhibited the growth of B. suis in culture and macrophages.…”
Section: Applications Of Pnamentioning
confidence: 99%
See 1 more Smart Citation
“…Rajasekaran et al have studied the inhibition of Brucella suis growth using PNA linked covalently to cell-penetrating peptides (CPPs) [2]. After 24 hour of treatment, Brucella genes are involved in DNA, RNA, cell envelope, fatty acid and protein synthesis that are inhibited the growth of B. suis in culture and macrophages.…”
Section: Applications Of Pnamentioning
confidence: 99%
“…Peptide Nucleic Acid (PNA) are single stranded which potentially mimic DNA capable of hybridizing to complementary DNA, RNA or PNA [2,3]. PNAs have high chemical stability and specificity [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Results are expressed as mean ± SEM of several independent experiments. engineering has been established for Brucella (Rajasekaran et al 2013). They have used peptide nucleic acids to inhibit the growth of Brucella suis in pure culture and in infected murine macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…They readily cross the bacterial cell membranes when coupled with a cell-penetrating peptide. Rajasekaran et al [97] reported growth inhibition of B. suis by PNAs, both in cell-free medium and in murine macrophages. In tryptic soy broth, the inhibitory PNAs were those targeting the genes kdtA (coding for a transferase affecting lipid A), tsf (elongation factor Ts), polA (DNA polymerase I), and rpoB (subunit B of RNA polymerase).…”
Section: Peptide Nucleic Acidsmentioning
confidence: 99%